Analytical Study of the Science Book for the Ninth Grade of Basic Education in Libya - Al-Otairish, Um Almeer Faraj; Al-Fazzani, Abdullah Ahmed; Ghmeidh, Hanan Hussein; Abu-Hajar, Fathi Mansour (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The study analyzes the content of the third chapter on human reproduction in the science book for the ninth grade in Libya. A sample of 11 topics in biology was studied. After consulting specialists, the students prepared a content analysis form consisting of 6 axes and 8 branches. The study found a defect in the vertical sequence of topics, making it difficult to understand the stages of reproduction. The study found a lack of logical progression in the curriculum, hindering students’ understanding of relationships between topics. The connection between basic concepts and theories was weak, causing difficulty in comprehending their interconnectedness. However, the reproduction chapter relates closely to real-life, with strong links to students’ daily experiences. Additionally, there is a weakness in the quality of questions that measure higher mental abilities, such as application, analysis, and creativity. A variety of educational strategies can enhance students’ understanding of interrelationships between concepts. The study recommends analyzing ninth grade science curriculum, reconsidering topic sequence, and providing applications and activities to enhance learners’ mental abilities.